The grammar of criminal law. Volume two, International criminal law - Fletcher, George P. (New York, NY : Oxford University Press, 2019)
This second volume of 'The Grammar of Criminal Law' addresses international criminal law and its importance for future international cooperation. The emphasis is on the concepts that provide the essential building blocks for all systems of criminal law.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 12, 2019).
Keywords: International criminal law; Law; Laws of specific jurisdictions & specific areas of law